The Effect of Workload and Compensation on the Work Stress of Employees of PT. Puja Perkasa - Dewi Listiorini; Harries Madiistriyatno; Ericho Agil Nugraha (Journal of Social Research, 2024)
This study aims to determine and analyze the effect of workload and compensation on work stress at PT. Mighty Puja. The things raised in this study are: a) how big is the influence of workload on work stress at PT. Puja Perkasa, b) how big is the influence of compensation on work stress at PT. Puja Perkasa, c) how big is the influence of workload and compensation on work stress at PT.Puja Perkasa. To determine the effect of the independent variable on the dependent variable partially used t test and to determine the effect of the independent variable on the dependent variable simultaneously used ANOVA. The sample used in this study were 35 people who were saturated samples. The data collection methods used are literature study, documentation and questionnaires. The results of this study indicate that with an alpha error degree of 0.05 through the -t test, it turns out that the workload variable significantly affects employee work stress, and compensation significantly affects employee work stress. Simultaneously through the ANOVA test, the two variables have a positive and significant effect on employee work stress.